UPAYA INDONESIA DALAM MEMPROTEKSI PRODUK LOKAL DI PASAR E-COMMERCE INDONESIA - Afifah Khairani; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The dominance of imported products in the Indonesian E-Commerce market has become a problem in last few years. Prices, and uniqueness that are better than local products cause Indonesian consumers to choose imported products and make local products unable to compete in the E-Commerce market. If this situation is allowed to continue, it will threaten the national interests. For this reason, this research was conducted to show the actions taken by the Indonesian government together with E-Commerce platforms in Indonesia in protecting domestic products from the dominance of imported products in the Indonesian E-Commerce market. This research used qualitative methods, with data collection techniques through library research sourced from books, journals, documents, websites and social media. This research uses the perspective of mercantilism and the theory of protectionism. The results of this research show the application of de minimis value for imported products, digitalization and export programs through E-Commerce, and also the blocking of product categories in Lazada and Shopee as Indonesia's actions in protecting local products with e-commerce platforms. These actions can limit the entry of imported products and reduce the dominance of imported products so that local products can enter and compete in the Indonesian E-Commerce market. Keywords: Protectionism, E-Commerce, Local Products, Imported Products, Indonesia.